Dendritic structured palladium complexes: magnetically retrievable, highly efficient heterogeneous nanocatalyst for Suzuki and Heck cross-coupling reactions. Issue 15 (21st March 2022) - Sheikh, Safoora; Nasseri, Mohammad Ali; Chahkandi, Mohammad; Reiser, Oliver; Allahresani, Ali
Abstract : The recyclable nanomagnetic Pd-complex PAMAM G0 -Pd@γ-Fe2 O3 is reported for catalytic C–C cross-coupling reactions of challenging substrates. Abstract : The recyclable nanomagnetic Pd-complex PAMAM G0 -Pd@γ-Fe2 O3 is reported for catalytic C–C cross-coupling reactions of challenging substrates. Mainly, a great variety of aryl chlorides can be used as substrates for Suzuki–Miyaura and Mizoroki–Heck reactions under mild reaction conditions (60–90 °C) and low catalyst loading (<1 mol% Pd) in aqueous media. The presence of numerous polar groups in the polymer matrix increases the solubility of the catalyst in water, thus facilitating its operation in aqueous environments. The immobilization of the catalyst on the surface of a magnetic platform allows its effective recovery and reuse without significant loss of catalytic activity for at least six cycles with total leaching of <1% palladium metal, meeting the requirements for acceptable metal residues in the pharmaceutical industry.